METHODOLOGICAL BASES OF DETERMINATION OF COMPETITIVENESS ON THE DIFFERENT LEVELS OF ECONOMIC RELATIONS - Moroz, O. V.; Stasenko, D. V. (Visnyk of Vinnytsia Politechnical Institute, 2015)
Types and factors of competitative relations are considered in the field of economics. Indexes and parameters of competitiveness of commodity, enterprise, and industry are described. The basic factors of competitiveness are defined on the different levels of competitive relations.